Mechanism of influence of molecular hydrogen on the function of the proximal tubule of the nephron in irritatable bowel syndrome - Rohovyi, Yurii; Tsitrin, Volf; Bilooka, Yula; Arkchipova, Ludmila; Bilookiy, Vyacheslav (Journal of Education, Health and Sport, 2021)
Aim. To find out a pathophysiological protective role of influence of molecular hydrogen on a functional condition of a proximal tubule of kidneys at an irritable bowel syndrome. Materials and methods. 60 patients with irritable bowel syndrome were examined. Men - 18, women - 42 aged from 28 to 62 years. Of which: with irritable bowel syndrome with constipation were - 28 patients, irritable bowel syndrome with diarrhea - 32. The control group consisted of 25 almost healthy patients. General clinical (Likert scale), functional (proximal reabsorption of sodium ions in the kidneys), enzyme-linked immunosorbent assay (concentration of cytokines in blood plasma: tumor necrosis factor-a, interleukin-1β, interleukin-6), microbiological (рopulation levels of anaerobic B. Bifidum, B. lactis in lg CFO/g in the lumen of the colon), biochemical (the total, enzymatic fibrinolytic activity of urine) research methods were used. All patients received molecular hydrogen in the form of an aqueous solution in the amount of 1 liter per day in four doses of 250 ml for 7 days with a concentration of H2 1.0 - 1.2 ppm and redox potential from -250 to -350 mV, which was obtained using a generator of a new generation of antioxidant solution saturated with hydrogen Blue Water 900 (Korea), mode 1. Statistical data processing was performed using computer programs "Statgrafics" and "Exel 7.0". Results and discussion. The protective effect of molecular hydrogen improves the functional state of the proximal renal tubule in irritable bowel syndrome due to its high permeability and selective antioxidant activity against hydroxyl radical and peroxynitrite, which contributes to the rupture of large and small vicious circles in the combined pathological process.